2005
DOI: 10.1016/j.theriogenology.2004.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Decay of sperm obtained from epididymes of wild ruminants depending on postmortem time

Abstract: We have carried out a study on the effect of postmortem time (PT) in some characteristics of epididymal sperm salvaged from hunted Iberian red deer and roe deer. Testis were collected, identified, refrigerated down to 5 degrees C, and sent to our laboratory by the wardens of the hunting reserves. This way, samples were delivered at different times postmortem. Sperm were extracted from the cauda epididymis by means of cuts. Analyzed parameters were: osmolality, pH, motility-both subjectively and with CASA, HOS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
52
1
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 26 publications
4
52
1
4
Order By: Relevance
“…A viable alternative to these methods is the postmortem recovery of spermatozoa during the hunting season. It has been proven that semen from wild ruminants, including roe deer, that is kept at low temperatures (5 o C) in the epididymis postmortem and is subsequently obtained from the cauda epididymis, maintains good quality for a long time after the death of the animal (Martinez-Pastor et al 2005a, Martinez-Pastor et al 2005b. The effect of season on epididymal spermatozoa recovered postmortem has also been investigated.…”
mentioning
confidence: 99%
“…A viable alternative to these methods is the postmortem recovery of spermatozoa during the hunting season. It has been proven that semen from wild ruminants, including roe deer, that is kept at low temperatures (5 o C) in the epididymis postmortem and is subsequently obtained from the cauda epididymis, maintains good quality for a long time after the death of the animal (Martinez-Pastor et al 2005a, Martinez-Pastor et al 2005b. The effect of season on epididymal spermatozoa recovered postmortem has also been investigated.…”
mentioning
confidence: 99%
“…armazenamento no epidídimo após a morte tem sido demonstrado em várias pesquisas com diferentes espécies (FERNÁNDEZ-SANTOS et., 2009, MARTINEZ-PASTOR et al, 2005, KAABI et al, 2003. Em seu estudo com Capra pyrenaica hispânica, SANTIAGO-MORENO et al (2007) constataram que a queda na qualidade dos espermatozóides está primariamente correlacionada com a queda da motilidade, sendo este o principal parâmetro afetado.…”
Section: Resultsunclassified
“…This depreciation is a result of spermatozoa aging and epididymides tissue degeneration and decomposition process (Martinez-Pastor et al, 2005b). Studies in rats revealed that degenerative testicular changes start approximately six hours after death, but in the epididymis, these alterations only begin 12 hours after death (Songsasen et al, 1998).…”
Section: Discussionmentioning
confidence: 99%